Emergency Readmission among Children with Chronic Conditions: A Scoping Review - Thika Marliana; Sugeng Hadisaputra; Yeti Patiroh; Restikaningrum; Fauziah Rudhiati (Journal of Scientific Insights, 2026)
Children with chronic conditions are at increased risk of emergency hospital readmission because of disease complexity, recurrent exacerbations, technology dependence, fragmented continuity of care, and socioeconomic vulnerability. Emergency readmissions contribute substantially to healthcare utilization, caregiver burden, and poorer pediatric health outcomes. This scoping review aimed to map and synthesize evidence regarding determinants, utilization patterns, and prevention strategies associated with emergency readmission among children with chronic conditions. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guideline. Literature searches were conducted across PubMed/MEDLINE, Scopus, Web of Science, CINAHL, Cochrane Library, SpringerLink, and ScienceDirect for studies published between 2010 and 2025. Of 412 identified records, 28 eligible reports were included following screening, eligibility assessment, and data charting. The included studies consisted predominantly of retrospective cohort studies, administrative database analyses, systematic reviews, and observational studies conducted mainly in high-income countries. Major factors associated with emergency readmission included complex chronic conditions, prolonged length of stay, technology dependence, prior healthcare utilization, inadequate discharge planning, weak care-transition continuity, socioeconomic disadvantage, race and insurance disparities, and limited caregiver readiness. Children with asthma, diabetes, sickle cell disease, neurological disorders, cancer, respiratory illness, and pediatric intensive care unit exposure demonstrated the highest readmission risk. Multifaceted discharge interventions, transitional-care programs, family-centered education, telehealth follow-up, and integrated care coordination showed potential to reduce avoidable readmissions. Overall, pediatric emergency readmission represents a multidimensional healthcare challenge requiring integrated clinical, family-centered, and healthcare-system interventions to strengthen continuity of care and reduce preventable rehospitalization.